Fe,Mg-Codoped Bismuth Tantalate Pyrochlores: Crystal Structure, Thermal Stability, Optical and Electrical Properties, XPS, NEXAFS, ESR, and 57Fe Mössbauer Spectroscopy Study - N. A. Zhuk; M. G. Krzhizhanovskaya; A. V. Koroleva; V. G. Semenov; A. A. Selyutin; A. M. Lebedev; S. V. Nekipelov; D. V. Sivkov; V. V. Kharton; V. P. Lutoev; B. A. Makeev (Inorganics, 2022)
The effect of Fe and Mg-codoping on the crystal structure, optical and dielectric properties of bismuth tantalate-based pyrochlores has been studied. Samples of Bi2MgxFe1−xTa2O9.5−Δ (x ≤ 0.7) are characterized by a porous dendrite-like microstructure. Fe,Mg-codoped bismuth tantalate pyrochlores are thermally stable up to a temperature of 1140 °C (x = 1). The Bi2Mg0.5Fe0.5Ta2O9.5−Δ thermal expansion coefficient increases uniformly and weakly from 3.6 to 9.3 × 10−6 °C−1 (30–1050 °C). The unit cell parameter of solid solutions increases uniformly from 10.5009(1) Å (x = 0.3) up to 10.5225(7) Å (x = 0.7). The structural parameters of disordered pyrochlore are determined by the Rietveld method (sp. gr. Fd<semantics><mover accent="true">3¯</mover></semantics>m:2 (227), Z = 8). According to near edge X-ray absorption fine structure and X-ray photoelectron spectroscopy data, ions in solid solutions are in the charge states Bi (+3), Mg (+2), Fe (+3), Ta (+5-δ). The Mössbauer spectrum is represented by a symmetric doublet with parameters IS = 0.365 ± 0.0020 mm/s, QS = 0.604 ± 0.034 mm/s, related to Fe3+ ions in regular axial octahedral positions. The samples exhibit the properties of dielectrics. The permittivity and the tangent of dielectric losses at 20 °C increases with the growth of iron content in the samples in the range of 28.5–30.5 and 0.001 (1 MHz). The width of the band gap of the obtained materials for direct allowed electronic transitions is in the range of 2.16(5)–2.41(5) eV. The studied samples satisfy the condition of efficient conversion of solar energy into an electrical one and are promising as catalysts and light-absorbing elements for solar panels.